Implications of Next Step Blockchain Applications for Accounting and Legal Practitioners: A Case Study - Sean Stein Smith (Australasian Accounting, Business and Finance Journal, 2019)
Perceived price volatility of cryptocurrencies may distract practitioners from further developments in the blockchain space that may generate audit and other implications. As next step applications and developments are built on top of existing blockchain programming, the potential implications for both accounting and legal practitioners may be substantive. Especially as different blockchain tools and platforms become more robust and conducive for business and transactional use, the importance of being able to attest and report on this information will move closer toward the mainstream. This article discusses the rise of blockchain applications in a manner applicable for both practitioners and academics, as well as the implications these applications will have on attestation and compliance reporting.
Keywords: Blockchain; accounting; cryptocurrency; reporting; innovation.